Penipuan Sebagai Hasil Manipulasi Dunia Maya di Indonesia - Abdul Azizun Nafi; Naufal Tsabit; Nur Aini Rakhmawati; Regita Ayu Cahyani Zulaikhah; Ufaira Khanzahasna Nanfaiq Nadhifa (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2019)
The presence of social media provides a lot of information, ranging from the ease of exchanging messages and information, to users who want to publish their work in order to be acknowledged by people, eliminate restrictions and can expand interchangeable discourse. Ideally, interactions that occur between individuals are based on individuals against other individuals because each one will not involve anything harmful. Through research conducted in the context of social media, it is hoped that people will have a more comprehensive understanding of social media in their lives and how to be decent. This study aims to find out how situations can be carried out in social interactions in society that use social media.